SUFFERING THE ABSOLUTE COMPETENCY OF THE COURT OF THE NIAGA FOLLOWING APPLICATION REQUESTS - Kurniawan, Muhammad Arief (Universitas Tadulako, 2019)
ABSTRACTÂ The acts member 30 of 1999 about arbitration explains if there is there is a civil dispute containing the arbitration clause must be completed in the arbitration forum, the district court must reject the petition to the resolve the dispute because the parties volantarily agree on dispute resolution process through an abritation institution. But what if there is bankrupty dispute whereas in article 303 of the acts number 37 of 2004 about bankruptcy and posponement of debt payment obligations explain that if there is a bankrupty dispute was process through a commercial court must include an arbitration clause. This research discused the power of convenant law that contain an arbitration clause on business disputesÂ and commarcial court jurisdiction in resolving a bankcrupty dispute whose agreement contains an arbitratin clause using normative juridical research method. The research results show that the commercial court has absolute competence in resolving bankruptcy disputes even though in includes an arbitration clause ; it is contained in article 303 of the Bankruptcy law which has complied with article 2 paragraph 1 of bankruptcy law. The intent of explain Article 303 of the law on Bankruptcy and delays in debt repayment obligation provide reinforcement on comptence of commercial courts in the settlement of bankruptcy disputes, the elements of article 2, paragraph 1 have been fulfilled, the jurisdiction of the commercial court that resolves the bankruptcy dispute even though it includes an arbitration clauseÂ Keywords : Authorithy of Competency and Bankruptcy